Effectiveness Model of Marketing Communication of Bank Sumut Syariah in Increasing Public Interest in Saving at Bank Sumut Syariah KCP Binjai - Melati Muslim; Mailin Mailin; Hasnun Jauhari Ritonga (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study aims to analyze the marketing communication model implemented by Bank Sumut Syariah KCP Binjai in increasing public interest in saving. The research is motivated by persistent problems of limited public understanding, skepticism, and trust issues toward Islamic banking products, which negatively affect saving intentions. A descriptive qualitative method was employed, using in-depth interviews, observations, and documentation involving branch leaders, account officers, and customer service staff. Data were analyzed using the Miles and Huberman interactive model, supported by triangulation to ensure data validity. The results indicate that Bank Sumut Syariah KCP Binjai employs a relational, value-based marketing communication model rather than a transactional approach. Face-to-face communication is identified as the most effective strategy, supported by a structured six-step sales process and the application of Islamic communication principles, namely qaulan layyinan, qaulan sadidan, and qaulan balighan. These principles strengthen credibility, build customer trust, and enhance customer satisfaction, which in turn increases public interest in saving. The study concludes that ethical, effective, and sharia-compliant marketing communication plays a significant role in fostering the sustainable growth of Islamic banking in Indonesia.